1995
DOI: 10.1007/bf01245389
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between suicide and myocardial infarction with regard to changing physical environmental conditions

Abstract: In recent years, the possible association of changes in mortality from cardiovascular disease and myocardial infarction (MI) and deaths related to violence and the suicide rate has been repeatedly discussed. This study examined the relationship between cosmic physical changes (solar, geomagnetic and other space activity parameters) and changes in the total number of in-hospital and MI-related deaths and deaths from suicide to determine if a relationship exists between the distribution of total and MI-related d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 20 publications
1
21
0
1
Order By: Relevance
“…No association between stroke-related death and solar activity but significant negative correla tion with GMA in men < 74 years old were found in Lithuania [2], A study in Israel demonstrated no signifi cant correlation between monthly hospital stroke mortali ty rates and 10 cosmophysical parameters, including solar and geophysical activities [5], but suggested a negative relationship between stroke-related admissions of men aged below 65 and GMA on the day of stroke onset [2], In these studies, however, the analyses were based on calcu lating of correlation coefficients and estimated monthly stroke-related deaths or admissions, and changes of geo physical parameters for preceding days were not taken into account. In this regard, conclusions of hospital-based studies on the relationship between stroke and environ mental factors are difficult to interpret because of selec tion bias [19], whereas mortality studies do not provide information about stroke occurrence and may be deter mined by complications of stroke [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No association between stroke-related death and solar activity but significant negative correla tion with GMA in men < 74 years old were found in Lithuania [2], A study in Israel demonstrated no signifi cant correlation between monthly hospital stroke mortali ty rates and 10 cosmophysical parameters, including solar and geophysical activities [5], but suggested a negative relationship between stroke-related admissions of men aged below 65 and GMA on the day of stroke onset [2], In these studies, however, the analyses were based on calcu lating of correlation coefficients and estimated monthly stroke-related deaths or admissions, and changes of geo physical parameters for preceding days were not taken into account. In this regard, conclusions of hospital-based studies on the relationship between stroke and environ mental factors are difficult to interpret because of selec tion bias [19], whereas mortality studies do not provide information about stroke occurrence and may be deter mined by complications of stroke [20].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that older and youn ger age groups of men and women are equally sensitive to the effects of geomagnetic factors and have common physiological mechanisms reponsible for their pathologic reaction to fluctuations of geophysical parameters stud ied. Although these mechanisms are not fully understood, the involvement of blood pressure changes [1,3], cardiac arrhythmias [5,6], platelet and leukocyte aggregation [4,6,7] have been suggested. We suggest that large fluctua tions of solar and geomagnetic activities on the day pre ceding stroke onset may act as triggers for underlying pathologic mechanisms leading to stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В противоположность, кли-ницисты из Индии обнаружили высокую прямую корреляцию между количеством госпитализаций по поводу сердечно-сосудистых заболеваний и геомагнитными возмущениями, также ими была установлена взаимосвязь между ежедневным ин-дексом геомагнитной активности и количеством инфарктов миокарда [21]. Исследователи из Изра-иля наблюдали прямую корреляцию между смерт-ностью от ИБС и солнечной активностью [22]. Так-же, исследования, проведенные в Литве, показали взаимосвязь между летальностью от сердечно-со-судистой патологии и геомагнитными бурями [23].…”
Section: Discussionunclassified
“…The variation of the air ion levels has been hypothesized as a stress factor acting on children [18], as well as the correlation between the change of meteorological conditions and the onset of myocardial infarction [19]. Many relevant chronobiological studies about the influence of high altitude on some physiological parameters (pressure of blood, heart rate, circadian and infradian cardiovascular rhythms, arterial stiffness and neurocardio-pulmonary function, etc.…”
Section: Extremely Weak Fieldsmentioning
confidence: 99%